RadioSource.NET: Case-study of a Collaborative Land-Grant Internet Audio Project - Kathleen Sohar; Ashley M. Wood; Roberto Ramirez (Journal of Applied Communications, 2002)
RadioSource.NET (http://radiosource.net) is a Web-portal news site for land-grant university radio programming. The project is a collaborative venture among university communication departments with the following goals: to share resources; increase online distribution; and promote access to agricultural and natural and life science research. This article is a case study of RadioSource.NET. The evolution of the RadioSource.NET project is examined with emphasis on the process of establishing and maintaining online collaborative partnerships within academia. The project’s development is described and discussed, and Wheeler, Valacich, Alavi, and Vogel’s (1995) framework for technology-mediated interinstitutional relationships for collaborative learning is used to help organize information and evaluate the project’s effectiveness. RadioSource.NET project is an example of successful university collaboration in new media. By utilizing a flexible system design, RadioSource.NET capitalizes on collaborative strengths such as increased innovation and efficiency, and it is anticipated that the project model can serve as a useful resource for other online collaborative endeavors utilizing emerging technologies.